2002
DOI: 10.1081/bip-120014567
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sensitivity and Similarity in Bridging Studies

Abstract: In pharmaceutical industry, the sponsors are interested in bringing their drug products from one region (e.g., the United States of America) to another region (e.g., Asian Pacific) to increase the exclusivity of the drug products in the marketplace. However, it is a concern whether the clinical results can be extrapolated from the target patient population in one region to a similar but different patient population in a new region due to a possible difference in ethnic factors. The International Conference on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…A clinical trial without sufficient sample size may not provide a desired reproducibility probability (6)(7)(8). In other words, the observed clinical results may not be reproducible at a certain level of significance.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial without sufficient sample size may not provide a desired reproducibility probability (6)(7)(8). In other words, the observed clinical results may not be reproducible at a certain level of significance.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex interaction among the drugs' pharmacological class, indication, and demography of the population [86], the ICH E5 guideline does not provide definitive criteria for evaluation of a drug's ethnic sensitivity in terms of the evaluating the complete clinical data package or assessing the similarity of clinical results between regions [87]. Various statistical models and strategies have been proposed to assess sensitivities and similarities in ethnicities [87,88,89]; however, no gold standard has yet been established.…”
Section: Ethnically Sensitive or Insensitive?mentioning
confidence: 99%
“…Various statistical models and strategies have been proposed to assess sensitivities and similarities in ethnicities [87,88,89]; however, no gold standard has yet been established. Specific methodology for extrapolating foreign clinical data is not provided, either.…”
Section: Ethnically Sensitive or Insensitive?mentioning
confidence: 99%
“…He also suggested that the result from the new region is consistent with the previous results if it falls within the previous experience. Chow et al (2002) employed the reproducibility probability and generalizability to assess the necessity of bridging studies in the new region. proposed a hierarchical model approach to incorporating the foreign bridging information into the data generated by the bridging study in the new region.…”
Section: Introductionmentioning
confidence: 99%